2020
DOI: 10.3390/genes12010024
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment Combination of IGF and EGF Promotes Hair Growth in the Angora Rabbit

Abstract: The hair follicle (HF) growth cycle is a complex, multistep biological process, for which dysfunction affects hair-related diseases in humans and wool production in animals. In this study, a treatment combination of 10 ng/mL insulin-like growth factor-1 (IGF-1) and 20 ng/mL epidermal growth factor (EGF) significantly increased the elongation length of hair shafts for cultured HFs. The combined treatment of IGF-1 and EGF enhanced the proliferation of HFs and promoted HF growth and development in vitro. In vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, the specific effect of chemokines needs to be further studied. Epidermal growth factor (EGF) has been identified in follicular differentiation (du Cros, 1993) and promotion of the transition of the hair cycle from telogen to anagen, as well as growth of the hair shaft (Zhao et al, 2020). Rendl et al (2008) found that when DPCs are cultured in a medium containing BMP4 in vitro, there is a significant increase in hair follicle formation, hair growth, and alkaline phosphatase expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific effect of chemokines needs to be further studied. Epidermal growth factor (EGF) has been identified in follicular differentiation (du Cros, 1993) and promotion of the transition of the hair cycle from telogen to anagen, as well as growth of the hair shaft (Zhao et al, 2020). Rendl et al (2008) found that when DPCs are cultured in a medium containing BMP4 in vitro, there is a significant increase in hair follicle formation, hair growth, and alkaline phosphatase expression.…”
Section: Discussionmentioning
confidence: 99%
“…ErbB1 ligand EGF growth factors have wide utilization from fundamental research to state-of-the-art therapies 15 17 . However, recombinant production of EGF domain growth factors has been a challenging task, demanding either eukaryotic systems, such as yeast 17 , 18 , mammalian cell lineages 19 21 , or fusion with ancillary proteins 22 – 26 or even in vitro renaturing procedures 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…LEF1 is a downstream factor of the Wnt signaling pathway and is expressed in inner and outer root sheath cells, hair stromal cells, and dermis. LEF1 is also highly expressed during the growth period and can promote the growth and development of hair ( 47 ). This study has the same results.…”
Section: Discussionmentioning
confidence: 99%